On Collusion and Industry Size - Escrihuela-Villar, Marc (2011)
In this paper we investigate the connection between the number of competitors and the sustainability of collusion within the context of a infinitely repeated symmetric Cournot model where only a subset of firms cooperate. We show that, in our model, an increase in the number of cartel firms may increase collusion likelihood by diminishing the negative effects for collusion of the existence of a competitive fringe. Also, we show that an increase in the number of fringe firms makes collusion harder to sustain.